Stroke Therapy With Sensor Games Accelerometer And Gyroscope - Nur Trihadi Utomo (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2020)
Stroke is a disease that has a long-term impact on people who experience it. Not only "sudden attacks" are feared, but also the consequences that follow. The condition of paralysis in certain limbs will certainly be very disturbing and even hamper one's life activities. The rehabilitation process takes a long time, so the patient experiences boredom. In the rehabilitation process there are several tools needed by post-stroke patients such as the use of movement aids and using memory training aids such as brain games.The accelerometer sensor and gyroscope sensor can be used to control post-stroke therapy games. With this stroke therapy game, patients are expected to be happier to carry out the stroke therapy process. This tool makes stroke therapy fun and can be done at home.